Sustaining the benefits of intravenous ketamine with behavioural activation therapy for depression: A case series - Jennifer L. Phillips; Pierre Blier; Jeanne Talbot (Journal of Affective Disorders Reports, 2023)
Background: Despite advances in treatments for depression, approximately one third of patients do not benefit from available therapies. Intravenous ketamine is a novel intervention that can yield rapid yet transient antidepressant effects. Behavioural activation (BA) therapy for depression has been shown to be effective in preventing relapse of major depressive episodes. In this pilot study, we examined whether antidepressant response achieved through repeated ketamine infusions could be maintained with BA. Methods: In this case series, patients with treatment-resistant depression who met antidepressant response criteria in a clinical trial of repeated ketamine infusions subsequently completed 12–17 sessions of BA. Depressive symptoms were measured at each session with the Beck Depression Inventory-II (BDI-II). Secondary outcomes included changes in work and social adjustment, suicidal ideation, and anxiety. Results: Ten of the 13 participants who initiated BA completed the full course of psychotherapy. These participants showed significant improvement in self-reported depressive symptoms (p = 0.007) and work and social adjustment scores (p<0.001) with BA. The 6 participants who started BA therapy prior to relapse of depressive symptoms following cessation of ketamine sustained the clinical gains achieved with ketamine. Limitations: The small sample size and lack of control group limit the conclusions. Conclusions: The transient period of increased mood after repeated ketamine treatment offers a window of opportunity to intervene with psychotherapy such as BA. A better understanding of how to best integrate psychological treatments with pharmacological treatment, particularly the novel use of rapid-acting medications such as ketamine is an unmet clinical need and promising research area.